مدى أهمية المدخل المقاولاتي في تدويل نشاط الصناعات الصغيرة والمتوسطة الجزائر The Importance Of The Entrepreneurial Approach In The Internationalization Of The Activity Of Small And Medium Industries Algeria - جعفر, صليحة; جوامع, اسماعين; غقال, الياس (جامعة الوادي - University of Eloued, 2018)
أصبحت المقاولاتية أو ريادة الأعمال من أهم مفاتيح النجاح في العصر الحديث في قطاع الأعمال، ذلك أن روح المبادرة التي يتميز بها الأفراد الراغبين في النجاح مع التطور الكبير في عالم الأفكار يجعل المقاولاتية مدخل مهم جدا يسعى كل أصحاب الصناعات الصغيرة والمتوسطة والذين يؤمنون بالمجازفة وروح الفردية هو الملاذ الأخير أو ربما الآمن من أجل نجاحهم في تدويل نشاط شركاتهم وتمكينها من الوصول العالمية. ولقد أبدى الكثير من المفكرين الإقتصاديين إهتمامهم بهذا المدخل – خاصة للصناعات الصغيرة والمتوسطة – وحاولوا وضع نظريات متكاملة تبحث في أهمية المدخل المقاولاتي وخاصة لأصحاب أو رواد الصناعات الصغيرة والمتوسطة. في هذه الورقة سوف يحاول الباحثين التعريف بنظرية المنظم الدولي (المقاول الدولي، أو رائد الأعمال الدولي) التي بحثت في هذا المجال، وسوف تكون إشكالية هذه الورقة حول، ما مدى أهمية المدخل المقاولاتي في تدويل نشاط الصناعات الصغيرة والمتوسطة؟ سوف نحاول من جهة أخرة معرفة مدى قدرة أو رغبة الصناعات الصغيرة والمتوسطة الجزائرية في تبني هذا المدخل من أجل تدويل نشاطها في الخارج، وفتح منافذ دولية لها. Becoming an entrepreneur or entrepreneurship the most important keys to success in the modern business era, so that the spirit of the initiative, which is characterized by people who want to succeed with the great development in the world of ideas makes entrepreneurial entry is very important to seek by all owners and those who believe in person at risk and the spirit of small and medium industries is or may be a last resort to ensure the success of the internationalization of their activity and allow global access. And have shown a lot of interest for this input economic thinkers - especially small and medium enterprises - and tried to develop an integrated theory are looking at the importance of entrepreneurship and private entry to the owners or small and medium-sized entrepreneurs In this article, researchers are trying to promote international organizer of theory (International Consultant, or a company of international standing), which has examined this area, and risks being problematic on this paper, the importance of entry activity entrepreneurship in the internationalization of small and medium-sized enterprises? We will try to find from the point of ability or willingness of small and medium industries in the Algerian adopt this approach in order to internationalize their overseas operations, and the opening of international end markets.
مقال
Keywords: التدويل، الصناعات الصغيرة والمتوسطة، المدخل المقاولاتي، نظرية المنظم الدولي. internationalization of small and medium industries, entrepreneurial entry, organized international theory